Field notes contributed by W. Ross Silcock, spring 1982 - Silcock, W. Rosset al (1982)
Field notes were contributed by W. Ross Silcock. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed